The Synergistic Enhancement of Electromagnetic Interference Shielding Polymer Composites using Carbon Nanofiber-Metal Oxide Hybrid Fillers - Teguh Endah Saraswati; Wijang Wisnu Raharjo; Dini Deviana Saputri (UNIVERSITAS SEBELAS MARET (UNS), 2025)
In this modern era, humans cannot be separated from utilizing electronic devices. The unwanted noise or disturbance problem in electronic devices is majorly caused by Electromagnetic Interference (EMI). Recent technology and materials are being developed to manufacture EMI shielding composites. Carbon nanomaterial-based composites have become a very attractive material because of their lightweight, incredible mechanical, thermal, and conductivity properties. Carbon nanofibers (CNFs) and metal oxides are promising combination materials that reveal unique properties of both components to enhance shielding effectiveness. This combination of CNFs and metal oxides results in a synergistic effect, where the conductive CNFs enhances the reflection of EMI, and the metal oxides contribute to the absorption and attenuation of the waves. In this review article, the authors focus on the extensive discussion about the synthesis method of producing CNFs, some studies that combine CNFs and metal oxide, and some reports about using CNFs-metal oxide as a hybrid filler in the EMI shielding composites.